Jawapan

2016-06-04T16:01:28+08:00
(2x+4)(x+1)=k(x-1)
2x^2  + 2x + 4x + 4 + kx + k = 0
2x^2 + ( 6 + k ) x + 4 + k = 0
x^2 + ( 6 + k ) x / 2 + ( 4 + k ) / 2 = 0

sor = - 6 - k ,     por = 4 + k / 2
a + b = 3 + m ,  (a)(b) = 3m
- 6 - k = 3 + m ,  3m = 4 + k / 2
                           6m = 4 + k
                           k = 6m - 4

- 6 - 6m + 4 = 3 + m
7m = - 5
m = - 5/7

k = 6(-5/7) - 4
k = - 8/2/7
k = 58/7
I've done that.. But, it is not the correct answer.. m=4, k=20
at lest ckpla thanks -_-
sorry.. forgot to say that.. anyway, thx for the answer.. and thx bcause you tried it too.. I will share the correct way with you when I got it.. Thx and sorry.. Hope you didn't save any grudge towards me.
i dont like that
sorry again.. I didn't mean to do that.. sorry